2010
DOI: 10.4103/0970-0358.70727
|View full text |Cite
|
Sign up to set email alerts
|

Management of post burn hand deformities

Abstract: The hand is ranked among the three most frequent sites of burns scar contracture deformity. One of the major determinants of the quality of life in burns survivors is the functionality of the hands. Burns deformities, although largely preventable, nevertheless do occur when appropriate treatment is not provided in the acute situation or when they are part of a major burns. Reconstructive procedures can greatly improve the function of the hands. Appropriate choice of procedures and timing of surgery followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…10,24,25 In our series we used Z/V-Y advancement flaps, free skin graft, free flaps and cross finger flaps.…”
Section: Discussionmentioning
confidence: 99%
“…10,24,25 In our series we used Z/V-Y advancement flaps, free skin graft, free flaps and cross finger flaps.…”
Section: Discussionmentioning
confidence: 99%
“…A number of methods using basic reconstructive techniques have been proposed which include contracture release and grafting, cross finger flaps, side finger flaps, Z-plasty, V-Y advancement flaps and local advancement flaps. [3] Fufa et al in their study concluded that the mainstays of management of these contractures include complete surgical excision of scar tissue and resurfacing of the resultant soft tissue defect, most commonly with full-thickness skin grafts. If scar contracture release results in major exposure of the tendons or joints, distant tissue transfer may be required.…”
Section: Age In Yearsmentioning
confidence: 99%
“…Sabapathy S.R were of the opinion that the problem of post burn contracture is largely preventable by good initial care, which would include elevation of the hand, appropriate splinting, early grafting of deep burns and supervised physiotherapy. [3] Some authors. [1] have observed that despite appropriate initial management, contractures are common.…”
Section: Age In Yearsmentioning
confidence: 99%
See 2 more Smart Citations